And soon I heard a roaring wind : a natural history of moving air - Streever, Bill (Little, Brown and Company, 2016)
"Offers entertaining and science-based observations on the wind, from the world's first forecasts, to Chaos Theory, wind-riding spiders, wind-sculpted landscapes and wind-generated power. By the best-selling author of Cold and Heat,"--NoveList.